Economic Growth, Poverty, Urbanization, and the Small and Medium Enterprises (SMEs) in Indonesia: Analysis of Cointegration and Causality - Hadi Jauhari; Periansya Periansya (Binus Business Review, 2021)
In Indonesia, poverty is still considered a serious problem, even though the number of poor people continues to decline significantly. The research aimed to investigate whether there was cointegration between the role of Small and Medium Enterprises (SMEs), economic growth, and poverty alleviation or not in Indonesia. Â Secondary data were compiled from annual data in 2000-2019. Data analysis applied the cointegration test and Vector Error Correction Model (VECM) test. The results show a one-way causality between poverty and economic growth, urbanization and economic growth, the role of SMEs and economic growth, and the role of SMEs and poverty. In addition, the results of the VECM analysis suggest that the role of SMEs has a positive effect on poverty in the first year. It means that it takes a year to find out the impact of the increasing role of SMEs on poverty at the later stage. The research has several implications for government, namely: (i) compiling work programs that touch the community directly and strengthen the development of local wisdom products, (ii) conducting more intense training, (iii) emphasizing on improving the quality and standards of local wisdom products, and (iv) building rural infrastructure that can facilitate the economic processes in the village.